Development and sensory evaluation of soyamusa: a soybeanplantain baby food - Oyewusi, F.; Ozumba, A.; Ogundipe, H.; Osifo, B.; Lukambi, F.; Ogazi, P. (International Society for Horticultural Science, 2000)
Appropriate technologies were used to process plantain and soybean into flour which were used for the formulation of ‘Soyamusa’, a soybean-plantain baby food that requires little cooking. Extruded and non-extruded soybean grits were produced and mixed with plantain flour in varying proportions to determine the blend that would give the required energy and protein level in baby foods. A mixture of sugar, vitamins and minerals was added to improve the taste and to meet the recommended daily vitamin and mineral requirements for babies. The final blend was subjected to nutritional and sensory evaluations. The sensory test was to determine the acceptability of the two products of ‘Soyamusa’ and compare them with other popular market brands. It was found that a mixture of 60% plantain flour, 32% soybean grit and 8% sugar produced a blend whose proximate analysis showed 15.8% protein, 8.0% fat, and 72.8% carbohydrate with an energy content of 457.4 kcal per 100g. The sixteen weaning Wister rats on ‘Soyamusa’ had normal growth, packed cell volume and white blood cell count. Hemagglutination test did not indicate any immunological reaction against ‘Soyamusa’. Results of the comparative assessment of the two samples for color, flavor, consistency, mouthful, taste and overall acceptability did not show any significant difference (P > 0.05). However, the samples differ significantly in all attributes (P < 0.01) from the two popular market brands but were equally acceptable.